THE ANALYSIS OF IMPLICATURE MEANING ON MALANG ONE WAY REGULATION PROTEST 2013 - VINADA, OCSA FEBRIAN BAYU (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Pragmatics, Implicature, Linguistics & Physical context, Social Context Language is used any time by a person in communication process. In fact many people use different ways to express anything in their mind. Implicature is one of the ways by implicating a meaning and producing hidden meaning. Therefore this study has problems which  are : 1. What is the implicated meaning in Malang oneway protest? ; 2. What are the reasons and the purposes of the residents in making the protest?. This study discovers an intended meaning from the protest banners which were collected when Malang One Way regulation 2013 was applied by using Linguistics Context, Physical Context and Social Context.  The writer collected the data by photographing many mounted protest banners in Jl. MT Haryono and Jl. Mayjend Pandjaitan (Betek) and choose some data that contain implicated meaning. In analyzing process, this research using descriptive qualitative method that requires the writer to interpret and then describes the intended meaning behind the data with his background knowledge and the phenomena happen. Furthermore, this study finds out that the data contains implicated meaning and represents residents idea of dissatisfaction to Malang One Way regulation 2013. They tend to implied meaning packed on protest. In this study, the reader will find Linguistic Context, Physical Context, and Social Context theory used by the writer to discover any intended meaning, reason, and purposes.  The writer suggests to the next researcher interested in a similar topic which is implicature to use Relevance Theory from Sperber and Wilson. This theory use background knowledge and context to build an exact meaning on implicature. Thewriter also suggest to use another data in a scope of art such as modern or traditionalsong lyrics, title, or script of drama.